1650 Is There a Place for Medical Students at Organ Retrieval? 4 Years' Experience at a Single Centre. (12th October 2021) - Duck, E; Schofield, E
Abstract: Aim: Medical students at a hospital with a national organ retrieval service (NORS) had the unique opportunity to attend organ retrieval. This retrospective survey investigated how attendance affected students' desire to pursue a career in surgery, and what they learnt from the experience. Method: Clinical medical students were invited to sign-up to shifts with the regional NORS team. If notified of a potential organ donation event the NORS co-ordinator would inform the medical student, who would then join the retrieval team and travel with them to the donation site. An electronic survey was later distributed to students, whether or not the donation proceeded. This survey collected both quantitative and qualitative information about the students' experiences. Results: 51 responses were collected from students who attended proceeding organ donations between January 2015 and October 2019. 100% of students found it a useful learning experience and would recommend it to their peers. 98% were able to scrub in for the retrieval procedure. Common learning points were improved understanding of the process of organ retrieval (n = 34), and anatomy (n = 15). Following experience of organ retrieval 59% reported being more likely to pursue a career in transplant surgery and 69% reported being more likely to pursue any surgical career. Conclusions: Medical students should be included in organ retrieval, as it not only benefits their learning, but also increases interest in surgical careers. Given that only two out of the sixteen UK NORS teams involve medical students currently, there is scope for much greater adoption of student retrieval rotas.